2007
DOI: 10.1007/s00221-007-0897-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-sensory integration of spatio-temporal segmentation cues: one plus one does not always equal two

Abstract: How are multiple, multi-sensory stimuli combined for use in segmenting spatio-temporal events? For an answer, we measured the effect of various auditory or visual stimuli, in isolation or in combination, on a bistable percept of visual motion ("bouncing" vs. "streaming"). To minimize individual differences, the physical properties of stimuli were adjusted to reflect individual subjects' sensitivity to each cue in isolation. When put into combination, perceptual influences that had been equipotent in isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…The persistence of reported bouncing on sound trials in spite of progressively greater texture density differences observed in Experiment 1 is surprising in light of the modality appropriateness hypothesis (e.g., Welch & Warren, 1980;Soto-Faraco, Spence, Lloyd, & Kingstone, 2004;Heron, Whitaker, & McGraw, 2004;Zhou, Wong, & Sekuler, 2007), which posits that the resolution of a multisensory display should be determined by information to the sensory modality that provides the most accurate estimate of the attribute. Vision is assumed to provide more accurate information about the location and motion of objects than audition and therefore should determine the resolution of our unambiguous displays.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The persistence of reported bouncing on sound trials in spite of progressively greater texture density differences observed in Experiment 1 is surprising in light of the modality appropriateness hypothesis (e.g., Welch & Warren, 1980;Soto-Faraco, Spence, Lloyd, & Kingstone, 2004;Heron, Whitaker, & McGraw, 2004;Zhou, Wong, & Sekuler, 2007), which posits that the resolution of a multisensory display should be determined by information to the sensory modality that provides the most accurate estimate of the attribute. Vision is assumed to provide more accurate information about the location and motion of objects than audition and therefore should determine the resolution of our unambiguous displays.…”
Section: Discussionmentioning
confidence: 88%
“…Another study by Zhou et al (2007) is relevant. These authors investigated the efficacy of two auditory cues (timing relative to the point of coincidence, auditory intensity) and two visual cues (luminance change at coincidence, pause in motion at coincidence) as well as their combinations in influencing the resolution of ambiguous stream bounce displays.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the luminance of pixels that do not correspond to the moving target (i.e., the points off the diagonals in Fig 2B, left) should be darker than average for them to trigger more likely a bounce response. In other words, this indicates that light stimuli moving against a dark background are more likely perceived as bouncing (see [36]). Additionally, the luminance kernel has more energy prior to the intersection than after.…”
Section: Resultsmentioning
confidence: 99%
“…The result of such motion energy computation is then combined with auditory information and recent perceptual memory into a single proxy variable representing the overall evidence towards one interpretation or the other. This is done in the following way: In line with current models of sensory integration [36, 44], assuming neural noise to be independent across the channels and normally distributed, we modeled sensory integration of visual motion energy, auditory signals, and recent perceptual memory as weighed linear integration. To make the stream-bounce information provided by the different channels (motion energy, audio signal, memory) directly comparable, linear coefficients ω i consisted of a combination of both weights and scaling factors [31, 45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation